2010
DOI: 10.1001/archinternmed.2009.417
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Level and Kidney Function in US Adolescents

Abstract: Background Chronic, high-level lead exposure is a known risk factor for kidney disease. The effect of current low-level environmental lead exposure is less well known, particularly among children, a population generally free from kidney disease risk factors such as hypertension and diabetes mellitus. Therefore, in this study, we investigated the association between lead exposure and kidney function in a representative sample of US adolescents. Methods Participants included 769 adolescents aged 12 to 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 73 publications
1
49
0
Order By: Relevance
“…However, excessive exposure to it could cause a variety of toxic effects, among which is its adverse influence on the kidney. An increasing number of studies have also indicated the unexpected effects and pathogenic mechanisms of Pb on renal function [3][4][5]. Among the various pathogenic mechanisms of renal injury, oxidative stress influences glomerular structure and function mainly depending upon the effect of reactive oxygen species (ROS) on mesangial and endothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive exposure to it could cause a variety of toxic effects, among which is its adverse influence on the kidney. An increasing number of studies have also indicated the unexpected effects and pathogenic mechanisms of Pb on renal function [3][4][5]. Among the various pathogenic mechanisms of renal injury, oxidative stress influences glomerular structure and function mainly depending upon the effect of reactive oxygen species (ROS) on mesangial and endothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cross-sectional studies in adults have demonstrated a significant positive association between blood lead level and serum creatinine [62-64], as well as increased all-cause and cardiovascular mortality [65]. An analysis of 769 adolescents participating in the 1988–1994 NHANES with median blood lead and cystatin C-based eGFR levels of 1.5 μg/dL and 112.9 mL/ min/1.73 m 2 , respectively, identified a statistically significant, negative association between blood lead level and kidney function [66]. In fully adjusted models, cystatin C-based eGFR was lower (−6.6 mL/min/1.73 m 2 ; 95 % CI −0.7 to −12.6) in children with lead levels in the highest quartile (≥3.0 μg/dL) compared with those in the lowest quartile (<1 μg/dL).…”
Section: Heavy Metal Nephrotoxicantsmentioning
confidence: 99%
“…This data lends itself well to cross-sectional studies. The association between lead levels in children and estimated glomerular filtration rate (GFR) was examined among 769 children who participated in the survey from 1988 to 1994 [3]. As can be observed in Fig.…”
Section: Case Seriesmentioning
confidence: 99%
“…Data points for the scatterplot represent adjusted blood lead and estimated GFR values. The horizontal axis is in the log scale (From Fadrowski and Navas-Acien [3], figure) simultaneously, and the investigator must infer cause and effect relationships because the temporal sequence cannot be established. In a case-control design, an attempt to establish a temporal relationship between the outcome and exposure is made by starting with a population of persons with and without the outcome and then working backward to examine suspected exposures.…”
Section: Case Seriesmentioning
confidence: 99%